PENERAPAN REWARD UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - Nely Hartika (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
This study discusses the application of reward in the learning process in order to improve the learning achievement of students of accounting class X in SMK Negeri 1 Ciruas on economic and business subjects aiming to find out how the application of rewards in learning to improve learning achievement. Learning treatment in the form of reward giving is one type of approach in the process of teaching and learning activities that can provide stimulus to students to be more academically achievers in economics and business subjects. Academic achievement is the cognitive ability that begins with enthusiasm and the emergence of student enthusiasm in dealing with the process of teaching and learning activities.This research was conducted at SMK Negeri 1 Ciruas- Serang Banten. The research method used is Classroom Action Research with a qualitative approach. The sample of this study were all students of class X accounting SMK Negeri 1 Ciruas as many as 36 students.The results of this study indicate that there is an increase in learning achievement in economic and business subjects by using a learning approach with the application of rewards in class X Accounting students in SMK Negeri 1 Ciruas .This is evidenced by an increase in learning achievement in economics and business subjects by using a learning approach with the application of rewards in class X Accounting students in SMK Negeri 1 Ciruas. This is evidenced by an increase in the number of students who passed the Minimum completeness criteria by 28 people or 77.78%.